Baseline characteristics for CLARITY AD: A phase 3 placebo‐controlled, double‐blind, parallel‐group, 18‐month study evaluating lecanemab (ban2401) in early Alzheimer's disease. (31st December 2021) - Lynch, Shau Yu; Irizarry, Michael C; Dhadda, Shobha; Li, David JianJun; Kanekiyo, Michio; Bogoslovsky, Tanya; Gee, Michelle; Reyderman, Larisa; Kaplow, June; Rabe, Martin; Hodgkinson, Mark; Kramer, Lynn D; et al.
Abstract: Background: Lecanemab (BAN2401) is a humanized IgG1 monoclonal antibody that preferentially targets soluble aggregated Aβ. In a recent multinational, phase 2, double‐blind, placebo‐controlled, study utilizing a Bayesian design with response adaptive randomization, 10‐mg/kg bi‐weekly lecanemab reduced brain Ab levels and slowed decline in cognition and function on Alzheimer's Disease Composite Score (ADCOMS), Alzheimer's Disease Assessment Scale‐Cognitive Subscale (ADAS‐cog), and Clinical Dementia Rating‐Sum of Boxes (CDR‐SB) at 18 months in participants with early Alzheimer's disease (AD). Following these results, the CLARITY AD phase 3 study was designed to confirm the efficacy and safety of lecanemab in participants with early Alzheimer's disease. Herein, we describe the baseline characteristics for participants in the ongoing CLARITY AD study. Methods: CLARITY AD is an 18‐month treatment, multicenter, double‐blind, placebo‐controlled, parallel‐group study with open‐label extension in participants with early AD. Baseline clinical and demographic data were summarized descriptively and compared to the lecanemab phase 2 study population. Results: As of a data cutoff of January 6, 2021, 1540 participants were randomized in CLARITY AD. The median age of participants was 72 years (range: 50‐90 years), with 81% of participants 65 years of age or older. Overall, 52% of participants were female and 75% were Caucasian. Mean (SD) baseline values for clinical endpoints were 3.2 (1.3) for CDR‐SB, 0.4 (0.1) for ADCOMS, 25.4 (7.3) for ADAS‐Cog, 25.6 (2.2) for MMSE, and 0.6 (0.2) for Global CDR. Aggregate baseline characteristics are similar to the lecanemab phase 2 study (median age 72 years [range: 50‐90 years]; 80% 65 years of age or older; 50% female; 90% Caucasian; clinical endpoints: 3.0 [1.4] for CDR‐SB, 0.4 [0.2] for ADCOMS, 22.2 [7.4] for ADAS‐Cog, 25.6 [2.4] for MMSE, and 0.6 [0.2] for Global CDR). Comparisons of the study populations will be presented. Conclusion: Building on the encouraging findings from the lecanemab phase 2 study, the phase 3 CLARITY AD study is designed to confirm clinical efficacy and safety of lecanemab versus placebo in participants with early AD. Baseline characteristics after enrollment of 1540 participants are consistent with the phase 2 study and representative of an early AD population. Enrollment is ongoing.